The pathogenetic role of some cytokines in the development and course of various clinical forms of urinary tract infections in children - H.O. Lezhenko; N.A. Zakharchenko (Zaslavsky O.Yu., 2022)
Background. The purpose of the research: to study the content of interleukin-6 and interleukin-15 cytokines in the blood serum of children with urinary tract infection and to establish their pathogenetic role in the development of various clinical forms of the disease. Materials and methods. The study groups consisted of 84 children (mean age of 10.0 ± 1.3 years). The main group was divided into subgroups: the first one - 17 children with acute pyelonephritis, the second - 21 patients with chronic pyelonephritis, the third - 16 children with acute cystitis, the fourth subgroup - 10 patients with unspecified urinary tract infections. The control group included 20 relatively healthy children. The content of interleukin-6 and interleukin-15 was evaluated by enzyme-linked immunosorbent assay. Results. It was established that the development of acute urinary tract infections was accompanied by a high level of serum pro-inflammatory interleukin-6. We found the highest level in children with cystitis, which exceeded that of the control group by 2.8 times (р < 0.01). In children with acute pyelonephritis, this cytokine was 1.8 times higher (р < 0.05). However, patients with chronic pyelonephritis had only a tendency towards its increase (p > 0.05). Interleukin-15 in the main group was statistically higher than in controls (р < 0.05). In children of subgroups 3 and 4, its level did not differ from that of the control group (p > 0.05). However, in subgroups 1 (р < 0.05) and 2 (р < 0.01), we observed a statistically significant increase in interleukin-15 level. A direct correlation between interleukin-15 content and disease duration (r = 0.64, р < 0.05) was also found. Conclusions. The development of an acute inflammatory process in the urinary tract in children occurs against the background of a marked increase in the expression of interleukin-6, while a chronic inflammatory process develops with a statistically significant increase in the level of interleukin-15 in blood serum.